Homogeneous vs Biased IGM: Impact on Reionization - Raut, Dinesh (Frontiers in Astronomy and Space Sciences, 2021)
This paper considers the impact of large scale biasing of the IGM on reionization. The two simplest but extreme scenarios for IGM biasing are: an unbiased IGM which has a constant density and an IGM with density equal to the collapsed matter density. In this work, the relationship between the IGM density and the collapsed matter density is defined through an IGM bias parameter. The two extreme scenarios of homogeneous and perfectly biased IGM are produced for two extreme values of this bias parameter. It is found that, for the same level of reionization (i.e. for same global neutral hydrogen fraction), one could get very different 21cm brightness temperature distributions for different values of this bias parameter. These distributions could give an order of magnitude more or less power as compared to the uniform case. It is also found that there exists a critical value for the IGM bias parameter for which there could be a near washout of the structure in the 21cm brightness temperature distribution (i.e. zero power or a nearly uniform 21cm brightness temperature distribution). To address the problem, a new method of generating 21cm brightness temperature maps is used. The method uses the results of n-body simulations and then employs ray tracing to obtain the 21cm brightness temperature maps. Towards the end, a prescription for the IGM bias parameter is given. This is derived within the framework of the Press-Schechter theory.